Rise of Foreign Employment and Challenges Faced by Nepali Youth in the Domestic Job Market - Rai, Nisha; Khadka, Nishan; Rai, Mitma; Shrestha, Prabin; Lekhak, Meena; Shrestha, Menuka; Mahat, Dipak (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Noticeable increasing trend of Nepali youth migrating for employment opportunities divert researcher to investigate the increasing prevalence of Nepalese youth seeking employment abroad and the obstacles they face in pursuing careers within Nepal. The research utilized qualitative research methods, gathering data through interviews and analyzing it using thematic analysis techniques. The research in Kathmandu valley found that Nepalese youth are drawn to foreign employment due to factors like economic inequality, political instability, social pressures, and desire for better living conditions, family obligations, and aspirations for personal and professional advancement. However, they face challenges such as limited job opportunities, favoritism, and issues in the education system, lack of financial rewards for education, and instability in private sector jobs. These findings emphasize the need for effective strategies to create more job opportunities in Nepal, address systemic issues, and empower youth for long-term development in the country.